UPAYA MENGENALKAN KOSA KATA BAHASA INGGRIS MELALUI METODE STORY TELLING PADA ANAK USIA 4-5 TAHUN DI TK SMV JAKARTA BARAT - Gesang Indah Lestari; Fitria Budi Utami (Yaa Bunayya : Jurnal Pendidikan Anak Usia Dini, 2025)
The purpose of the research is to find out story models that are suitable for children aged 4-5 years and how to implement them in SMV Kindergarten so that children's English vocabulary increases. Adding English vocabulary in a tri-lingual school environment (Mandarin, English and Indonesian) will become more complicated when children start learning vocabulary from different languages. Because the meaning of one word can be interpreted differently, it is important for children to understand the vocabulary as a whole in one sentence or story. The method used in this research is the classroom action method which is carried out in two cycles. The results obtained from this research are that children aged 4-5 years can absorb and understand English vocabulary thoroughly and can use this vocabulary in everyday life. And children aged 4-5 years like stories told by their teachers using simple English modified by the teacher.